Depression and religious coping in patients with acute coronary syndrome in Turkey - ÇELİK, MELİKE (My University, 2022)
Psychological health problems such as depression, anxiety and feelings of distress are often seen in patients with acute coronary syndrome (ACS). Religious coping in dealing with psychological health problems is one of the methods commonly used by cardiac patients. This study was conducted to determine the depression levels and religious coping methods of individuals diagnosed with ACS and identify the relationship between their positive or negative religious coping methods and their depression levels. The descriptive and correlational study was conducted with 253 ACS patients. In the study, the depression levels of most patients were low, but 19.8% showed moderate-severe depressive symptoms. It was found that the patients adopted positive religious coping styles on a high level, but there was no significant relationship between positive religious coping and depression levels (p > 0.05). It is recommended that health professionals also closely monitor ACS patients for depressive symptoms after their diagnosis, encouraging patients to use positive religious coping styles to support their well-being and recovery against this life-threatening disease.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; İlahiyat; Social Sciences and Humanities; Sociology; Theology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); DİN; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); RELIGION; ARTS & HUMANITIES; Arts & Humanities (AHCI); İş Sağlığı ve Terapisi; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Halk, Çevre ve İş Sağlığı; Epidemiyoloji; Dini çalışmalar; Koruma; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sağlık Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Safety Research; Health (social science); General Social Sciences; Public Health, Environmental and Occupational Health; Epidemiology; Religious Studies; Conservation; Arts and Humanities (miscellaneous); General Arts and Humanities; Health Sciences; Social Sciences & Humanities; Acute coronary syndrome; Depression; Religious coping; HEART-SURGERY; SPIRITUALITY; ANXIETY; ASSOCIATIONS; PREDICTORS; OUTCOMES